Exploring blockchain - based applications for digital copyright protection - Liu, Bin; Yasin, Megat Al Imran; Abdul Rahman, Saiful Nujaimi (Human Resource Management Academic Research Society, 2023)
This article provides a comprehensive review of the current landscape of digital copyright protection and the challenges it faces, particularly in the areas of registration and rights confirmation, authorized transactions, and monitoring and enforcement. It also explores the potential of blockchain technology as a solution to these challenges and analyzes the perspectives and strategies proposed by scholars. The review identifies three main research dimensions: a holistic approach to digital copyright protection, specific field perspectives, and technological advancements. Furthermore, the review highlights the importance of interdisciplinary collaboration and comprehensive exploration to further advance digital copyright protection. The findings emphasize the need to strengthen user education on copyright protection, balance the interests of creators and users, and continue evaluating the feasibility and effectiveness of blockchain technology in practical digital copyright protection scenarios.